Role of IMP3 Expression in Colorectal Carcinoma: An Immunohistochemical Study - ED Hassab El-Naby, Noha; Hashem Mohammed, Maisa; Mohammad Galal, Abdelrahman; Maher, Amira; Ahmed, Nagwa Abd El-Sadek (Asian Pacific Journal of Cancer Care, 2025)
Purpose: Colorectal carcinoma (CRC) ranks as the third most frequently diagnosed cancer globally and the second most common cause of cancer deaths. CRC is a major public health issue that is associated with high incidence and mortality rates. Insulin-like growth factor II m-RNA-binding protein 3 (IMP3) is an oncofetal RNA-binding protein that plays a key role in the carcinogenesis and progression of various neoplasms. Its overexpression is correlated with aggressive behavior and unfavorable prognosis of many cancers, so it can serve as a prognostic biomarker. This study aimed to evaluate the immunohistochemical (IHC) expression of IMP3 in CRC in relation to the available clinicopathological data to clarify its prognostic significance. Methods: Seventy specimens of CRC were included in this study. Immunohistochemistry (IHC) was used to evaluate IMP3 expression in CRC. A statistical analysis of the results was conducted to correlate IMP3 expression with the clinicopathological findings. Results: IMP3 expression was detected in 48 (68.6%) of the studied CRC cases. Statistically significant correlations were detected between IMP3 expression in relation to tumor grade (p=0.003), T stage (p<0.001), N stage (p=0.001), and lymphovascular invasion (LVI) (p=0.006). Conclusion: IMP3 upregulation in CRC is associated with an unfavorable prognosis; its overexpression is correlated with tumor progression and spread, so it could be tried as a therapeutic modality for CRC to reduce the tumor progression and improve the clinical outcome.